Succession of earthquakes in the Ebro Delta. A sequence to research pupils’ ideas and the prac tice of using evidence - Puig Mauriz, Blanca; Pérez Maceira, Jorge José; Montero Vilar, Santiago (Universidad Pedagógica y Tecnológica de Colombia, 2015)
A “socially live” issue related to Geology is dealt with: the controversy surrounding the succession of earthquakes in the Ebro Delta (Spain). This article examines both students’ ideas about earthquakes and the practice of using evidence in the context of choosing a causal explanation of Delta’s earthquakes. The study is part of the researches on reasoning about socioscientific issues in Geology. Three groups are involved: one belonging to CSE 4th grade (students aged from 16 to 17) and two to baccalaureate 1st grade (aged from 17 to 18). The results indicate that most of students understand an earthquake as a common phenomenon, and relate it exclusively to the tectonics plates. Regarding the controversy of Ebro Delta most choose as the cause of earthquakes the combination of natural causes and human activity, and focus on building an explanation, rather than justify their choice based on evidence.